An association between type A porcine endogenous retrovirus copy number and hematological parameters and gender in miniature pigs - R. B. Aitnazarov; S. V. Nikitin; G. V. Kontsevaya; M. I. Voevoda; N. S. Yudin (Вавиловский журнал генетики и селекции)
Pig is the most promising species for transplantation of organs and cells into humans, although implementation of xenotransplantation in clinical practice has been hindered by the risk of infecting the recipient with zoonotic infectious diseases. Porcine endogenous retroviruses (PERV) are capable of incorporating copies of DNA into the genome of a host cell. Based on the nucleotide sequence of the envelope gene (env), three main types of pig retrovirus, PERV-A, PERV-B and PERV-C, have been recognized, with PERV-A and PERV-B having the capability of infecting human cell lines in vitro. Selection for animals with low copy number of retroviruses in the genome using simple phenotypic indications is required for the widespread implementation of xenotransplantation. The objective of this study was to evaluate the correlation between PERV-A env gene copy number and hematological parameters, gender and coat  color in miniature pigs of the Institute of Cytology and Genetics (ICG) SB RAS. Reference values for eighteen blood parameters of miniature pigs were determined, including white blood cell count (WBC), red blood cell count (RBC), platelet count (PLT), absolute (LYM#) and relative (LYM%)  lymphocyte counts, absolute (MID#) and relative (MID%) monocyte, basophil and eosinophil counts, absolute (GRA#) and relative (GRA%) granulocyte counts, hematocrit (HCT) and thrombocrit (PCT), mean cell volume (MCV) and mean platelet volume (MPV). Males had significantly higher reference values for WBC, MID#, GRA# and red cell distribution width (RDW-CV) as compared to females. The mean corpuscular hemoglobin  concentration (MCHC) and platelet distribution width (PDW-CV) were significantly higher in female animals. No correlation between PERV-A env gene copy number and the coat color of  animals was detected, suggesting that retroviral insertion sites and genes that determine the coat color of miniature pigs, namely KIT (chromosome 8) and MC1R (chromosome 6), are either located far apart on same chromosome or on different chromosomes. The copy number of PERV-A env gene in males was lower than in females. Presence of multiple copies of PERV-A on the X-chromosome is the most probable cause of such gender-related differences in miniature pigs. Thus, male miniature pigs of ICG SB RAS should be the source of material for xenotransplantation.